Synchronous E-Learning for Effective Instructional Delivery as Perceived by Lecturers and Students of Adeyemi Federal University of Education, Ondo, Nigeria - Owolabi, Boludola Gbemisola; Akingbulu, Samson Pariola; Akinnusi, Ayorinde Emola (Teaching, Learning, and Development, 2026)
The study investigated the perception of lecturers and students on synchronous e-learning in Adeyemi Federal University of Education, Ondo. The sample size is 300 which comprised two hundred and fifty-nine (259) undergraduates and forty-one (41) lecturers. which was randomly selected. The research design to be adopted is descriptive survey. The instrument employed is questionnaire containing items on synchronous e-learning. The face and content validity was ascertained by giving the instrument to three experts in the fields of Educational Psychology and Counselling as well as test and measurement while reliability coefficient was established using Cronbach alpha. Frequency distribution, bar chart, mean, t-test and Analysis of Variance (ANOVA) were the statistical tools used for data analysis. A research question was raised, and two hypotheses were generated to guide the conduct of the study.  The findings revealed that there was no significant difference in the perception of students on synchronous e-learning based on gender; there was no significant difference in the perception of lecturers and students towards synchronous e-learning etc. Based on the findings, the   recommendations made were that there should be in-service training for teachers on the effective use of synchronous e-learning for instructional delivery; students should be enlightened on the proper involvement in synchronous e-learning; the school authority should support the Management Information System (MIS) unit to make the school community ICT-inclined for both the lecturers and students so as to encourage synchronous e-learning and other forms of e-learning for teaching-learning process etc.